Disruptive Strategy Programs in early Childhood Education (Docentes 2.0 Journal, 2026)
Early childhood education faces contemporary challenges that demand innovative and flexible pedagogical approaches capable of redefining traditional educational settings. The central purpose of this study was to systematically examine recent scientific literature on programs grounded in disruptive practices in early childhood education, aiming to identify emerging trends, evidence of educational impact, and implementation challenges, with particular attention to Latin American contexts, especially Ecuador. The research was conducted from an interpretive paradigm, using a systematic method, a qualitative approach, a narrative-thematic analytical documentary design, and a cross-sectional perspective. The analyzed sources, considered relevant based on preliminary searches, consisted of 83 documents from digital databases and academic repositories: Scielo, Redalyc, Latindex, DOAJ, and Dialnet. The results allowed for the identification of research focused on pedagogical innovation, play-based methodologies mediated by technology, STEAM approaches, the management of disruptive behaviors, and the use of artificial intelligence as an emerging pedagogical resource. From a total of 83 documents identified, a refinement process was carried out according to the established criteria, resulting in the selection of 37 relevant studies for the systematic review. The findings demonstrate favorable effects on motivation, holistic student development, self-regulation, and attention to vulnerable contexts, thereby confirming the achievement of the stated objective. Finally, the implications for teaching practice are analyzed, and guidelines are proposed to inform future research in early childhood education.
Keywords: Disruptive strategies; Early childhood education; Artificial intelligence